The origins of the state in Italy, 1300 - 1600 - Kirshner, Julius (Studies in European history from the Journal of modern history, 1996)
The state is "back in" / Julius Kirshner -- Legitimacy, discipline, and institutions : three necessary conditions for the birth of the modern state / Pierangelo Schiera -- The "private", the "public", the state / Giorgio Chittolini -- Law and jurists in the formation of the modern state in Italy / Aldo Mazzacane -- Center and Periphery / Elena Fasano Guarini -- The state and public finance : a hypothesis based on the history of late medieval Florence / Anthony Molho -- The courts / Trevor Dean -- Church, religion, and state in the early modern period / Roberto Bizzocchi -- The Italian League and the policy of the balance of power at the accession of Lorenzo de 'Medici